Pricing and quality level decisions of substitutable products in online and traditional selling channels: game‐theoretical approaches. (7th December 2017) - Taleizadeh, Ata Allah; Akhavizadegan, Faezeh; Ansarifar, Javad
Abstract: This study addresses a pricing problem of two substitutable products in a two‐echelon supply chain including two manufacturers and one retailer. The manufacturers sell their products through two distribution channels, namely traditional and Internet channels. The linear demand functions of products depend on selling prices, service value of channels, and quality level of products. Moreover, various market power structures are considered for the members of the supply chain. This study focuses on the specific game‐theoretical approaches to highlight the effect of market power structures and leadership between firms. The manufacturer–leader Stackelberg (MSS) game, retailer–leader Stackelberg game (RSS), manufacturer‐Bertrand competition (MSB), and retailer‐Bertrand competitions (RSB) are applied to analyze equilibrium solutions. The models help both manufacturers and retailer not only to maximize their profits but also to see the influences of their powers and decisions under different strategies. As a result, the leader has enough power to get higher profit, and the maximum profit of the whole supply chain is affected by the market powers of manufacturers and retailer. The best strategies for the retailer are those that are based on the RS games. The results illustrate that lower price does not lead to lower profit, and more sales does not necessarily result in higher profit. Moreover, the Bertrand strategy considered by the manufacturers to determine their optimal decisions is the best strategy from the customers' perspective.